2003
DOI: 10.1103/physreva.68.022322
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum computing in the presence of spontaneous emission by a combined dynamical decoupling and quantum-error-correction strategy

Abstract: A new method for quantum computation in the presence of spontaneous emission is proposed. The method combines strong and fast (dynamical decoupling) pulses and a quantum error correcting code that encodes n logical qubits into only n + 1 physical qubits. Universal, fault-tolerant, quantum computation is shown to be possible in this scheme using Hamiltonians relevant to a range of promising proposals for the physical implementation of quantum computers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We anticipate that reduction in multi-qubit errors will alleviate the restrictions placed by connectivity of the qubits as it will be possible to perform more SWAP gates without corrupting the states. In such scenarios, hybrid QEC-DD [38,45,46] methods could be experimentally assessed and would constitute an attractive near-term target for higher performance gains than is enabled by either scheme alone.…”
mentioning
confidence: 99%
“…We anticipate that reduction in multi-qubit errors will alleviate the restrictions placed by connectivity of the qubits as it will be possible to perform more SWAP gates without corrupting the states. In such scenarios, hybrid QEC-DD [38,45,46] methods could be experimentally assessed and would constitute an attractive near-term target for higher performance gains than is enabled by either scheme alone.…”
mentioning
confidence: 99%
“…Many proposals [19][20][21][22][23][24][25][26] have used the Born-Markov approximation or restrictions on the type of decoherence (e.g., symmetric and collective decoherence), even though some papers also considered DF subspaces that do not invoke the Born-Markov approximation and seems to be general regarding the type of decoherence [19]. Some well-known methods have been developed for protecting quantum systems from noise: dynamical decoupling and quantum error correction.…”
Section: Introductionmentioning
confidence: 99%
“…In dynamical decoupling, designed pulses are applied to the system for protection, allowing the damaging effects of noise to nearly average away, while in quantum error correction, protected logical qubits are encoded as collective states of many physical qubits to permit the detection and overturning of damage due to noise. Some authors considered combining these two methods of error control to explore quantum computing in DF conditions [20,23,27]. In addition, optimal control [28] and topological protection [29] have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, improvements in gate accuracy achieved by DD mean that more noise can be tolerated by a hybrid QEC-DD scheme than by QEC alone, and that invoking DD can reduce the overhead cost of QEC. While early studies identified various advantages [25][26][27], they did not address fault tolerance. A substantial step forward was taken in Ref.…”
mentioning
confidence: 99%